2021
DOI: 10.1109/ms.2020.3029468
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Software Testing Goes Serverless: Creating and Invoking Metamorphic Functions

Abstract: Our function-as-a-service (FaaS) framework transformed end users' questions into automated tests for scientific software. Our case study illustrates the FaaSification of scientific software testing and the importance of value-driven evaluations by focusing on real-world defect detection.MANY SCIENTIFIC RESEARCHERS rely on software to perform their research. In climate research, for instance, scientists and policy makers rely on code simulations to inform their recommendations and decisions. 1 Because scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For instances, in testing simulations, MT has been successfully adopted to test agent-based (ABM) and discrete-event (DES) simulations [26], hybrid ABM and DES systems [11], health care simulation [25], webenabled simulation [1], and simulator platform for self-driving cars [36,41]. In testing scientific software, MT is an effective technique to detect faults in simulation programs for designing nuclear power plants [14], bioinformatics programs [4], epidemiological models [31,33], chemical reaction networks for prototyping nano-scale molecular devices [13], matrix calculation programs [32], solvers for partial differential equations [3], multiple linear regression software [22], ocean modelling [16], storm water management model systems [19], machine learning-based hydro-logical models [40], Monte-Carlo computational programs [10,30], serverless scientific applications [20], as well as other types of scientific software [9,18,19,29]. For example, He et al [14] has found 33 bugs in simulation programs that are used to design and analyze nuclear power plants in a study that adopts MT.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, in testing simulations, MT has been successfully adopted to test agent-based (ABM) and discrete-event (DES) simulations [26], hybrid ABM and DES systems [11], health care simulation [25], webenabled simulation [1], and simulator platform for self-driving cars [36,41]. In testing scientific software, MT is an effective technique to detect faults in simulation programs for designing nuclear power plants [14], bioinformatics programs [4], epidemiological models [31,33], chemical reaction networks for prototyping nano-scale molecular devices [13], matrix calculation programs [32], solvers for partial differential equations [3], multiple linear regression software [22], ocean modelling [16], storm water management model systems [19], machine learning-based hydro-logical models [40], Monte-Carlo computational programs [10,30], serverless scientific applications [20], as well as other types of scientific software [9,18,19,29]. For example, He et al [14] has found 33 bugs in simulation programs that are used to design and analyze nuclear power plants in a study that adopts MT.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are more studies on testing hydrological modeling software using MT, such as Lin, Peng, et al. (2021) and Lin, Simon, and Niu (2021), the MRs used in these studies were not derived directly from hydrological knowledge of the system being modeled.…”
Section: Introductionmentioning
confidence: 99%